2015
DOI: 10.1002/cbm.1984
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of firesetters

Abstract: Our five-cluster solution with five subtypes of firesetters partially validates the proposed M-TTAF trajectories and suggests that for offenders with and without mental disorder, this classification may be useful. If further validated with larger and more diverse samples, the M-TTAF could provide guidance on staging evidence-based treatment. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…To test the hypotheses of this study, variables similar to those explored in extant research were identified (also see introduction and Supporting Information for a complete compilation of variables explored). Items were rated as being present whenever case files explicitly stated their presence or included diagnostic results proving their existence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To test the hypotheses of this study, variables similar to those explored in extant research were identified (also see introduction and Supporting Information for a complete compilation of variables explored). Items were rated as being present whenever case files explicitly stated their presence or included diagnostic results proving their existence.…”
Section: Methodsmentioning
confidence: 99%
“…In keeping with the traditional research approach of exploring arsonists in terms of their motives, personal, and crime scene characteristics, while also drawing on specific research on arsonists with SSD, we further hypothesize arsonists with SSD will differ from other offender patients with SSD in terms of their personal (H1A) and crime scene (H1B) characteristics as well as criminal motives (H1C). To test these hypotheses, we used similar variables as have been used in the research cited above (see Supporting Information for a complete compilation of variables explored).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a tendency in criminological and mental health literature to couple animal cruelty and firesetting as precursors to particularly adverse mental health and/or violent outcomes (Becker et al, ; Dalhuisen et al, ; Lindberg et al, ; Miller, ), but the rarity of each of these behaviours makes them elusive to study. Epidemiological studies based on the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) data, for instance, indicate a lifetime prevalence of animal cruelty of 1.8% (Vaughn et al, ) and of 1% for firesetting (Vaughn et al, ).…”
Section: Introductionmentioning
confidence: 99%